Spiritual Emotional Freedom Technique with Quality of life and Depression in HIV/AIDS Patients: Systematic Review - Firmansyah, Doddy; Gultom, Satriani; Dame, Artha Marisi; Suherlan, Herlan; Ernawati, Dedeh; Manurung, Sarida Surya; Kamil, Abdu Rahim (Journal Of Nursing Practice, 2021)
Background: Quality of life and depression in HIV patients is an impact that will be received by HIV patients if the intervention is not carried out properly, to reduce the impact that will occur to eliminate the worst impacts, HIV patients must always be motivated and approach in the form of counseling and other approaches such as spiritual emotional freedom technique.Purpose: The purpose of this study was to collect the right type of therapy or intervention to reduce depression rates due to psychological impacts on HIV patients and improve the quality of life of HIV patients.Methods: The design of this study uses a systematic review approach by collecting several articles from a selected database consisting of science direct, pubmed and proquest with articles published in 2016-2021. The search for articles was conducted by entering the words "Spiritual emotional freedom technique OR SEFT OR Counseling AND Depression AND Quality of life OR QOL AND HIV OR AIDS". The search articles were limited to inclusion criteria and exclusion criteria. The inclusion criteria in this study were HIV patients with low quality of life and depression. The study design was a randomized controlled trial and a quasi-experimental study, while the exclusion criteria were HIV patients without quality of life problems and depressive disorders, cross sectional and literature review.Results: The results of this study were the publication of articles, Science Direct articles 4513, proQuest 18862 article and 7350 pubmed article, 614 articles were deleted because duplicates 1560 were reviewed specifically and found 9 articles that matched the inclusion and exclusion criteria. Research that met the criteria was presented in a systematic table.Conclusion: it was found that there are several appropriate interventions that can be given to HIV/AIDS patients, one of which is counseling about the disease and the provision of spiritual emotional freedom technique therapy